(untitled) (Significação: Journal of Audiovisual Culture, 2003)
In this article, we define the signification notjust as a linguistic process but also as a process anchored to the set of action, including the ways of representative thinking, anterior to the discourse itself. We searched for an epistemological approach to the relations between practice, representation and discourse that allows a questionable state around the articulations between the discursive and non-discursive conducts, in a perspective of the meaning social production. Ou r aim is thinking the social knowledge production, including the specifically discursive, searching for, at the same time, elements to an epistemology of mediatic processes, which consider the discursive singularity. In order to make possible this approach, the article proposes a synthesis between the specified signification processes by the chosen discourse analysis (Charaudeau) and the suggested signification processes in the genetic theory (Piaget).